FAKTOR-FAKTOR YANG MEMPENGARUHI PENGANGGURAN TERSELUBUNG DI PERDESAAN JAWA TENGAH Analisis Data Sakernas 2007 - Dewi Hartina (Research Centre for Population, Indonesian Institute of Sciences, 2009)
Utilizing the 2007 National Employment Survey (Sakernas), this article aims to explore disguise unemployment in rural areas of Central Java. Several factors related to this issue namely sex, age, education level, household status, marital status and type of occupation were analyzed. Disguise unemployment is an important phenomenon, because it is not only seen from the amount of working hours but also the rate of income, thus disguise unemployment also related to productivity. Based on the 2007 Sakernas, disguised unemployment in rural Central Java are higher than those in rural areas of other Provinces in Java .. Generally, this study shows that education level and type of occupation are strongly influence the status of disguise unemployment. The higher education level is the lower chance of an individual to be disguise unemployment. Meanwhile, based on the type of occupation, agricultural workers have a more chance becoming disguise unemployment than the worker in manufacture and service sector. In addition, agriculture also has less productivity rate than other sectors. Thereby. increasing the agricultural productivity in rural Central Java will reduce indirectly the amount of disguise unemployment in this area, which then may improve the welfare of Central Java populations.Keywords: Unemployment, productivity; rural areas